Need Analysis for the Development of the SI-ECOFIS E-Worksheet Integrating Ecotheology and Education for Sustainable Development in Environmental Physics Courses - Yani Suryani (BIOCHEPHY: Journal of Science Education, 2026)
Environmental physics courses in higher education face challenges in integrating value-based ecological perspectives with scientific content. This study aimed to conduct a needs analysis as the initial stage in developing the SI-ECOFIS e-worksheet (Sustainable Integrated Ecotheological Environmental Physics), an electronic worksheet designed to integrate ecotheological perspectives and Education for Sustainable Development (ESD) principles. The study employed a research and development (R&D) approach using the ADDIE model, focusing on the analysis phase. The participants consisted of 75 Physics Education students, three physics lecturers, and three environmental education experts from UIN Raden Intan Lampung. Data were collected through questionnaires, interviews, document analysis, and classroom observations. The findings revealed that the existing environmental physics learning materials have not adequately integrated ecotheological perspectives or effectively fostered ESD competencies. In addition, students demonstrated a high level of digital readiness, with 87% using smartphones as learning tools, while two of the three lecturers expressed readiness to adopt ESD-oriented instruction materials. The needs analysis identified six essential components of SI-ECOFIS: ecotheological orientation, environmental physics content, contextual tasks, ESD competency activities, ecological value reflection, and collaborative action projects. These findings provide an empirical foundation for the subsequent design and development phases of the SI-ECOFIS e-worksheet within the ADDIE framework.